Correction and compensation of I/Q imbalance and multipath channel for OFDM receivers - Haq, K.; Chung, Kah-Seng (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper presents an adaptive scheme in overcoming signal distortion, caused by I/Q imbalance and multipath propagation, in an OFDM receiver. Estimation of I/Q imbalance and channel parameters is performed in the frequency domain with the aid of pilot tones. These estimated values are then used to adjust the gain and phase to reduce the distortion caused by I/Q imbalance. The resulting less distorted signal is then subjected to a simpler post compensation process to remove the effects of the multipath channel and any residue frequency-dependent I/Q imbalance. MATLAB simulations have demonstrated that the proposed approach provides substantial improvements to the system performance.